(untitled) (Conference Series, 2022)
This study aims to analyze and describe strategies for instilling the value of Christian Education in early childhood by introducing eco-literacy in using plastic waste media. Theoretically, this research helps add scientific studies related to Christian Education learning media and eco-literacy in early childhood by utilizing plastic waste in Manado City. This research is also expected to enrich scientific research in the field of eco-literacy in early childhood in Manado City and can be a reference for further research. This study uses a qualitative research method with a descriptive analysis approach based on library research. This research is located at GMIM Anugerah Tingkulu Kindergarten, Manado City, held from March to June 2022. The results of this study indicate that the introduction of the concept of eco-literacy in early childhood could be done through plastic waste media. Christian Education’s values observed in this research are Values of Gratitude, Values of Responsibility, and Communal Values.